The Use of Artificial Intelligence in Recruitment and Selection - Kuan, Xiu Ling, Yvonne (2018)
This qualitative research seeks to explore and attempt to provide a comprehensive overview on the use and impact of Artificial Intelligence (AI) in the Recruitment & Selection (R&S) process, as well as the receptiveness of recruiters in adopting AI technologies. 10 semi-structured interviews were conducted with recruiters from different sectors and industries. Study findings show that the use of AI technologies aid the R&S process by making the process more efficient, objective, and allowing for better engagement with applicants. It was also found that recruiters welcome the idea of using AI as opposed to studies that claimed that HR professionals are averse against it.